Weltgeschichte, Heilsgeschichte.: Umwälzungen in China als Folie missionarischer Geschichtskonstruktionen, 1900–1912 - Klein, Thoralf (Comparativ, 2009)
In contrast to other agents of imperialism, Protestant missionaries were not (or at least not primarily) committed to a modern, secular concept of history in the Enlightenment tradition. Rooted, for the most part, in pietism or evangelicalism, they saw world history as part of a much wider history of salvation that was ultimately a divine project. Salvation history implied a teleology that would inevitably culminate in the establishment of the Kingdom of God. World history, on the other hand, was not meaningless: For those who were able to “read” it, historical events provided clues to God’s eschatological programme; at the same time, they testified to the intervention of God in human history. In the missionary discourse, confrontations with the colonial ‘Other’ had the same function of providing examples to corroborate the construction of a history beyond human history. This becomes evident in my analysis of a case study from China, a country that was not formally colonized, but which was subjected to “Western” dominance. The coverage of two events (the Boxer War of 1900 / 01 and the Republican revolution of 1911/12) in the periodical Chinese Recorder, notwithstanding differences, shows how contemporary events were regarded as proving divine immanence in history. In so doing, it not only points to ways of coping with imperialistic anxieties, but also calls for a more nuanced understanding of colonial modernity as a formation that includes the seemingly premodern.